Museu da língua portuguesa: fruição e aprendizagem na relação interativa - Mafra, Priscila Zanganatto (2012)
This research was developed from an inquietude to investigate the interrelationships of Education, Arts, Culture and Technology in the spaces that go beyond the universe of the classroom. Transformations are investigated in the museum institution, covering the interactive museums, including the Football Museum and the Catavento Museum, preceding the focus of this study which lies on the research in the Portuguese Language Museum. Would it be a cultural mediator through its digital environments and interactive relationship with the public? What is the reaction of visitors when facing the Portuguese Language Museum and its digital environments? To answer those questions, under ethnographic inspiration, the research was conducted involving field observations of environments and visitors, involving interviews with museum professionals, and a participation in different educational activities promoted by the Portuguese Language Museum, besides documental research and research in the cyberspace, through the museum s website and social networks. The registers were made from the language of "words" and "images , analyzed, classified and interpreted from, based on the theoretical study. The wondering and use of the Portuguese language, the interactivity and cultural mediation in digital environments, show that the learning and enjoyment depend on the interest and participation of each visitor of the Museum of the Portuguese Language, which, in its environment and actions invite and provoke their audience to interact.